Progresive Assessment of teaching competences: Collaborative methodology to designe an intermediate profile - Yañez Monje, Verónica; Palma Troncoso, Marcela (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This article presents a methodology for the design and validation of an intermediate profile, which is used as a reference for the construction of the progressive evaluation of the teaching competencies established in the graduation profile of the study plan. It encompassed a number of phases, whose products were being validated by experts, within a systematic, reflective and collaborative procedure, in which academics and students were involved. This last aspect was considered pivotal to determine a profile of intermediate skills that would account for the know-how of a future teacher, for evidence-based decision-making.